The Utility of Employee Flows as a Driver of Marketing Productivity - Lee, Gregory (My University, 2009)
The movement or flow of employees into, around and out of organisations (‘employee flow’) has long been a central issue in human resource management and industrial psychology. This is especially so for the specific element of employee turnover, but also applies to staffing and internal talent development. Employee flow is especially salient in a South African context characterised by scarce skills. The voluminous literature on employee flow has tended to view each element such as recruitment or turnover separately, and has generally focused on internal outcomes (e.g. commitment or satisfaction). This thesis attempts to add two crucial features, namely EF as a whole system (i.e. inflows, intraorganisation flows and outflows of staff in conjunction), and customer-based outcomes. Something of a synthesis is thus sought between EF and ideas of marketing productivity. Marketing productivity has been proposed as one of the most important foci of the marketing discipline (Rust, Ambler, Carpenter, Kumar, & Srivastava, 2004; Sheth & Sisodia, 2002). It refers to links between marketing and organisational performance or value. Models such as the ‘service profit chain’ (Heskett, Sasser & Schlesinger, 1997) identify the antecedents of marketing productivity to be internal organisation characteristics such as staff satisfaction or loyalty. This thesis seeks to expand such models in the context of a system of EFs. Advanced decision theoretic utility theories of EF (e.g. Boudreau & Berger, 1985) allow for the complete, integrated value of employee movements over time to be modelled. Such a model is constructed and links to marketing metrics, notably service perceptions, investigated. Organisational value arising via the outcomes for customers are further iii investigated. Thus increased value of employee movements is proposed to generate organisational value, mediated by improved customer equity (e.g. Gelade & Young, 2005). An empirical, survey-based study was conducted to assess the model. EF was assessed in business-to-business relationships from the perspective of the customer using conceptions of decision theoretic utility analysis, and both intermediate and outcome-based customer perceptions of service quality used as dependent variables. Moderation effects from frequency of interaction and integration of the customer into the supply chain were also tested, as well as controls for characteristics of the transaction, organisation and industry. Results suggest that EF does significantly affect various stages of service quality provision, notably ‘potential quality’, which it appears mediates links to other aspects of service provision, especially final service outcomes. In addition, EF was also found to affect outcomes through the intermediate relational element of 'soft process quality', possibly highlighting the importance of relationship management and soft skills in B2B relationships. Employee outflows in particular showed evidence of relatively strong effects, possibly highlighting the ongoing salience of turnover, in particular effective identification and management of functional versus dysfunctional turnover instead of a sole focus on retention. Results were significantly stronger for service industries than others (presumably as service is the outcome), and when there were relatively few supplier contact staff (perhaps due to social networking, bonding, exchange or emotional contagion). This thesis adds substantially to the methodologies underlying service profit chain models. It explicitly included new constructs (EF utility). Contextually, it was the first proper test of this model in South Africa. Theoretical iv contributions arose from new inter-disciplinary syntheses of utility models, finally linking employee and customer utilities to the organisation. Ultimately, practical significance may arise for managerial models, estimating and justifying human resource interventions. Key words: Service-profit chain, marketing metrics, decision theoretic utility analysis, employee movement, employee flow, employee turnover, employee acquisition, employee separation, customer equity, customer satisfaction, customer retention, organisational performance, organisational value.
Keywords: marketing